Sheikh Abdurrauf Al-Singkili's Theological Thought and its Influence on the Understanding of Tawhid in Aceh Society - Hakim, Lukman (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Theological discourse is a unique and interesting field of Islamic studies that has colored intellectual debates and determined the dynamics of the Islamic world, both in the Middle East and in Nusantara. This study examines Sheikh Abdurrauf al-Singkili's theological thought contained in the book 'Umdat Al-Muhtajin Ila Suluk Maslak Al-Mufridin, which was intentionally written to guide the people of Aceh in their religious understanding during the theological polemic of the time, namely the issue of wujudiyah. This research focuses on the theological thought of the book and its influence on the practice of tawhid in Aceh society. The study found that the theological thought contained in the book is influenced by the Ash'ari theological school, characterized by the mention of Allah's attributes and the rejection of Jabariyya and Qadariyya. At the time, the book had an influence on the understanding of tawhid and the path to Allah, but its influence was lost as it was no longer used as a reference in the development of Islamic knowledge in the dayahs, which are known as the centers of tawhid studies in Aceh. This reality should serve as a reference that Acehnese scholars' theological thought can be re-studied in the development of Islamic studies, both in dayahs and Islamic universities.